Material Characterization and Micro-Modeling of a Historic Brick Masonry Pillar. Issue 7 (2nd October 2016) - Drougkas, Anastasios; Roca, Pere; Molins, Climent
ABSTRACT: A masonry pillar composed of solid clay bricks, cement mortar and infill is extracted from a historical structure and tested in concentric compression. It is subjected to cyclic and monotonic loads up to compressive failure. In parallel, samples are extracted from the pillar and are subjected to destructive tests. Non-destructive tests are performed on the pillar, as well. The properties of the constituent materials are critically examined and their role in the maximum load reached and the failure mode obtained are discussed. Finally, a finite element micro-model of the pillar is used for the simulation of the pillar test. The influence of the existing damage on the pillar is investigated using the model, resulting in a fair approximation of the global Young's modulus, maximum load and the failure mode. Highlights ● A brick masonry pillar extracted from a historical building is tested in compression. ● Material samples extracted from the pillar are characterized by mechanical tests. ● A finite element micro-model of the pillar is used for the simulation of the compressive test. ● The effect of damage on the compressive strength of the pillar is numerically investigated.